Impact of foaming conditions on quality for foam-mat drying of Butterfly pea flower by multiple regression analysis - Nguyễn Minh Thủy; Phung La Bao; Ngô Văn Tài; Võ Quang Minh (Plant Science Today, 2023)
In recent years, the Butterfly pea flower has been increasingly interested in its color and function. However, the preservation of the extract faced many difficulties; therefore, foam drying technology was applied to solve this problem. The study was conducted to determine the effect of foaming conditions, including albumin ratio, carboxymethyl cellulose (CMC) ratio, and whipping time on foam characteristics. At the same time, the multi-dimensional regression method was also used to determine the most suitable foaming conditions for the following process. The research results showed that all 3 factors strongly influenced the foaming process of pea flower extract. It could be concluded that the most suitable condition for foaming is to use 9.3% albumin, 0.79% CMC and stir for 19 min. Under these conditions, the foam expansion and stability were 584.79% and 96.44% respectively. The powder obtained from the foam drying of Butterfly pea flower extract was also analyzed for quality. The temperature of 65 oC for 4 hrs gave relatively high-quality powder with protein content, anthocyanin and antioxidant activity of 9.89 g/100g, 1.15 mg/g and 87.34% respectively. In conclusion, the foam-mat dried powder from butterfly pea flower extract is suitable for other processing processes, especially in the processing of folk cakes, pasta and bread industry.
Keywords: Proteins in Food Systems; Pickering emulsions and particle stabilization